2007
DOI: 10.1590/s0101-81752007000300017
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade biológica da comunidade de peixes no baixo rio das Mortes, Mato Grosso, Brasil

Abstract: O rio das Mortes é um dos principais cursos d’água do estado de Mato Grosso e o maior afluente, da margem esquerda, do rio Araguaia, sendo que a seção baixa do mesmo está inserida na planície do Bananal. Este estudo objetiva caracterizar ecologicamente a comunidade de peixes considerando um período sazonal: cheia e seca. A comunidade de peixes em estudo apresenta altos valores de diversidade (4,783 bits/indivíduos do Índice de Shannon-Wiener), riqueza de espécies (66 espécies amostradas) e abundância de indiví… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
1
13
1
3
Order By: Relevance
“…Novo Santo Antônio, a municipality located between the Mortes and Araguaia rivers, is the region’s principal arapaima fishery center, and the lakes found along the course of the Mortes River provide the bulk of the catch landed on the Araguaia River ( Kirsten et al, 2012 ). The municipality of São Félix do Araguaia is located at the confluence of the Mortes and Araguaia river, on the Bananal plain ( de Melo et al, 2007 ). Most of the arapaima fishermen of Mato Grosso are resident in this municipality ( Kirsten et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Novo Santo Antônio, a municipality located between the Mortes and Araguaia rivers, is the region’s principal arapaima fishery center, and the lakes found along the course of the Mortes River provide the bulk of the catch landed on the Araguaia River ( Kirsten et al, 2012 ). The municipality of São Félix do Araguaia is located at the confluence of the Mortes and Araguaia river, on the Bananal plain ( de Melo et al, 2007 ). Most of the arapaima fishermen of Mato Grosso are resident in this municipality ( Kirsten et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…The fish fauna present in the Araguaia-Tocantins basin is similar to that of the Amazon basin, though with greater number of endemic species (Tejerina-Garro et al 2002;Melo et al 2005). Among recent publications, Melo et al (2004) studied diet of 71 species of fish from a small stream of upper rio Araguaia; Benedito-Cecilio et al (2004) studied a dividing water area of the Parque Nacional das Emas, in the headwaters of the rivers Araguaia (Araguaia basin) and Anaconda (upper Paraná basin), resulting in an account of 18 species; Melo et al (2005) published a catalog comprising 51 medium to large sized fish species from rio das Mortes; Silva et al (2007) investigated the factors that influenced the fish community in the Bananal plain, and found 80 species; Melo et al (2007) found 72 species in the lower rio das Mortes. In the most recent study, Venere and Garutti (2011) listed 162 species in the Ichthyofauna of the rio Araguaia basin, states of Mato Grosso and Goiás, Brazil DOI: 10.15560/10.3.483 Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale migrations ensure dispersal and spawning and result in large densities of some species in the main channel of rivers during some periods of the year (Bonetto, 1963;Godoy, 1967;Bayley, 1973;Ribeiro, 1983;Carvalho & Mérona, 1986). Lateral migrations between the floodplain and the main channel of large rivers can be linked to feeding strategies as well as strategies for shelter (Cox-Fernandes & Mérona, 1988;Cox-Fernandes, 1997;Melo et al, 2007), which seasonally modify the relative abundance of fish populations in the assemblage.…”
Section: Introductionmentioning
confidence: 99%